Monitoring of Respirable Particulate among Workers Exposure in Paper Based Industry - Nur Athirah Afifa, M. L.; Norhidayah, Abdull; Leman, A.M.; Paiman, N.A. (2013)
Paper based industry may contribute to the respirable particulate (RP) that affects the air quality associated with the chronic health problem of workers. Respirable particulate (RP) fraction can be defined as the fraction of inhaled airborne particles that can penetrate beyond the terminal bronchioles into the gas-exchange region of the lungs (WHO, 2006). As a preliminary study, this research conducted the monitoring of RP at two selected area which are production line and packaging line. A personnel monitoring was applied to calculate the Time Weighted Average (TWA) of RP among workers. An area monitoring was also used to measure the concentration of RP in ambient air. The personnel monitoring depicts most of the workers were exposed to the higher TWA. The recorded TWAs are not complied to Occupational Safety and Health Agency (OSHA) and American Conference of Governmental Industrial Hygienists (ACGIH) standard, respectively. The area monitoring indicates that the concentrations of RP are higher during noon operation session. It concludes that the workers may have respiratory impairment due to the exposure of excessive RP. The environmental physical parameters indicate that the temperature is higher and the relative humidity and air velocity are slightly lower at production station. This study can be used as a platform for proposing some preventive measures to control the excessive RP in paper based industry.